A lost lady - Cather, Willa, 1873-1947. (New York : Vintage Books, 1990)
Mrs. Forrester, the resident aristocrat in the fading railroad town of Sweet Water, Nebraska, is widely admired for her attention to the conventions of her position as the wife of an executive, but privately she chafes at the restrictions that bind her to her much-older husband and their way of life.
Wilson's Fiction.
Adult
Keywords: Entertaining -- Nebraska -- Fiction; Frontier and pioneer life -- Nebraska -- Fiction; Upper class -- Nebraska -- Fiction; Entertaining -- Nebraska -- Fiction; Frontier and pioneer life -- Nebraska -- Fiction; Upper class -- Fiction